FAKTOR PENENTU KEBERHASILAN REHABILITASI SOSIAL BERBASIS KELUARGA: STUDI KASUS PADA ANAK-ANAK PEKERJA MIGRAN KABUPATEN INDRAMAYU - Rini Hartini Rinda; Mira Azzasyofia (Politeknik Kesejahteraan Sosial Bandung, 2021)
Family-based social rehabilitation of children is one of the flagship programs of the Indonesian government at this time, shifting institution-based social rehabilitation for children who need support and protection. Based on the understanding that the best child is in family care. The purpose of this study was to determine the factors that determine the success of family-based children's social rehabilitation, particularly case studies of children of Indonesian migrant workers who are separated from the care of their biological parents. In addition, it is also to determine the characteristics of migrant workers' children, what are the characteristics of the extended family providing care and how the family-based social rehabilitation process for children has been carried out. This study used a qualitative approach and descriptive method, the type of research was a case study on the children of Indramayu migrant workers who came from Taiwan with 6 informants who were determined using a purposive sample technique. The results showed that all children were separated from maternal care at an early age, the extended family who provided care were grandparents, aunts and aunts. The social rehabilitation process is carried out by improving the functioning of the family in meeting children's basic needs and foster care. The factors that influence the success of social rehabilitation are family acceptance, the attachment built by substitute figures, continuous communication between the child and the mother, the presence of family assistants who act as facilitators of the social rehabilitation process, and the support of the closest environment.